AKIBAT HUKUM TERHADAP PELAKU TINDAK PIDANA TERORISME DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM DI INDONESIA - Bagus Sulaksono (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
AbstractTerrorism is an act that uses violence or threats of violence that create an atmosphere of terror or widespread fear, which can cause mass casualties, and/or cause damage or destruction to strategic vital objects, the environment, public facilities, or international facilities with ideological, political, or security disturbance motives. Terrorism involves groups that attempt to overthrow certain regimes, correct group/national grievances, or undermine the international political order. The main element of terrorism is the existence of acts of violence, political differences being the main motive, taken either individually or in groups by spreading fear against the opposing party so that the ruling regime fulfills its demands. Terrorism is also carried out by killing the race of a nation because of feelings of revenge or political problems. Terrorism like this includes crimes against human rights, which deliberately destroy or destroy all or part of a national group or ethnic race. The regulation of criminal acts of terrorism according to positive law in Indonesia and Islamic law, namely in Law Number 5 of 2018, while Islamic law is based on the al-Qur’an and the Hadith of the Prophet. Criminal sanctions for criminal acts of terrorism according to positive law in Indonesia and Islamic law are : (1) Law Number 5 of 2018 in the form of imprisonment and capital punishment, and (2) Islamic law in the form of Jarimah hudud. This criminal act of terrorism is also included in the finger of qishash who is sentenced to death if there is no amnesty (amnesty). If the perpetrators surrendered and laid down their weapons, the suppression was stopped and they were rebels guaranteed the safety of their lives and assets, then the government (ulil amri) could forgive them or punish them with ta’zir punishment. Keywords :      Crime, Islamic Law, Legal Consequences, Perpetrators, Positive Law, Terrorism